Identifikasi Molekuler Udang Penaeid dengan Pendekatan DNA Barcoding - Saleky, Dandi; Dailami, Muhammad; Manan, Jemmy; Manumpil, Abraham Welliam (Politeknik Negeri Sambas, 2022)
Penaeid Shrimp (Crustacea: Decapoda) is an important fishery commodity in human life both in terms of economy, ecology, and nutrition. Penaeid shrimp are widely distributed and abundant on the coast of Merauke and become one of the leading commodities in the fisheries sector. The identification problem in the Penaeid shrimp group is a problem that still often occurs today. Identification problems are often not carried out because they are considered unimportant even though they can be important information for conservation and sustainable management. This study was conducted to identify the Penaeid Shrimp from Payum Beach, Merauke Regency, Papua by using a DNA barcoding approach with the Cytochrome Oxidase I Gene. The results of the analysis showed that the species of specimens was Mierspenaeopsis sculptilis (Heller, 1862) with a similarity level of 97.38%. Genetic distance and level of DNA similarity are very influential in phylogenetic reconstruction. Identification with DNA barcoding has succeeded in identifying species quickly and accurately and can be used to confirm previously identified species based on morphological characters.